Institutional Complexities in Organisations: A Theoretical Integration of Multiple Logics and the Locus of Paradoxical Tension - Sujeewa Damayanthi; Tharusha Gooneratne (Colombo Business Journal)
Organisations encounter a multiplicity of influences developing complexities that stem from competing or contradicting logics of the institutional field. When such influences enter organisations and interface with organisational actors’ sense-making, they create paradoxical tensions with implications for decision-making. This paper theorises how in the organisational field, multiple logics develop complexities and get intertwined with organisational actors’ sense-making, resulting in paradoxical tensions. It presents propositions leaning on a theoretical framework that integrates multiple logics and the locus of paradoxical tension. We propose that in an unstructured institutional field, organisational actors face increased tension, leading to a decision-making situation of either ‘acquire and adjust’ or ‘reject and maintain existing practices’. The selection of ‘acquire and adjust’ then results in a choice between ‘acquire’ (conformity) and ‘partial conformity or non-conformity’ to the prevailing logics in the field. Our integrative framework provides insights to future researchers for making sense of messy organisational realities amid broader influences.